Feasibility and effectiveness of basic lymphedema management in Leogane, Haiti, an area endemic for bancroftian filariasis. - David G Addiss; Jacky Louis-Charles; Jacquelin Roberts; Frederic Leconte; Joyanna M Wendt; Marie Denise Milord; Patrick J Lammie; Gerusa Dreyer (Public Library of Science (PLoS), 2010)
BACKGROUND: Approximately 14 million persons living in areas endemic for lymphatic filariasis have lymphedema of the leg. Clinical studies indicate that repeated episodes of bacterial acute dermatolymphangioadenitis (ADLA) lead to progression of lymphedema and that basic lymphedema management, which emphasizes hygiene, skin care, exercise, and leg elevation, can reduce ADLA frequency. However, few studies have prospectively evaluated the effectiveness of basic lymphedema management or assessed the role of compressive bandaging for lymphedema in resource-poor settings. METHODOLOGY/PRINCIPAL FINDINGS: Between 1995 and 1998, we prospectively monitored ADLA incidence and leg volume in 175 persons with lymphedema of the leg who enrolled in a lymphedema clinic in Leogane, Haiti, an area endemic for Wuchereria bancrofti. During the first phase of the study, when a major focus of the program was to reduce leg volume using compression bandages, ADLA incidence was 1.56 episodes per person-year. After March 1997, when hygiene and skin care were systematically emphasized and bandaging discouraged, ADLA incidence decreased to 0.48 episodes per person-year (P<0.0001). ADLA incidence was significantly associated with leg volume, stage of lymphedema, illiteracy, and use of compression bandages. Leg volume decreased in 78% of patients; over the entire study period, this reduction was statistically significant only for legs with stage 2 lymphedema (P = 0.01). CONCLUSIONS/SIGNIFICANCE: Basic lymphedema management, which emphasized hygiene and self-care, was associated with a 69% reduction in ADLA incidence. Use of compression bandages in this setting was associated with an increased risk of ADLA. Basic lymphedema management is feasible and effective in resource-limited areas that are endemic for lymphatic filariasis.